Necessary Life Skills for The Reinforcement of Positive Social Behavior in the Ninth- Grade's Physical Education and Sport Curriculum - Mecheri SOULEF; Nabila BRIK; Smail LAYES (Social Sciences Journal, 2021)
This study aimed to examine whether the physical education and sports curriculum involves the life skills necessary for the promotion of positive social behavior (i.e., communication skills, social skills and teamwork, psychological and moral skills) in ninth grade students, which corresponds to the middle-school fourth grade. Based on a content analysis, the results of our study showed that the inclusion of life skills necessary to support students’ positive social behavior in the physical education and sport curriculum was insufficient. This finding applies to both the life skills considered in our study and other secondary life skills as well.